Worldwide Trend in Taxation - Gałuszka, Jolanta (Trendy w polityce podatkowej na świecie, 2010)
The purpose of this paper is to analyse the direction of trends in the tax systems. The first part analyses the influence of globalisation on tax policy, the second one describes a phenomenon of international tax competition and the next introduces and evaluates the calibre of the current proposals to tackle tax competition, especially its harmful consequences. Governments around the world have pursued differenet economic policies. That diversity has created a wide range of economic outcomes - from glittering prosperity in some nations to abject poverty in others. Over the time, it has become clearer what sorts of economic policies, including tax policies, should be pursued to improve living standards.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 125, s. 27-36
Keywords: tax policy; fiscal burdens; tax competition; globalization